Evaluasi Sistem Penomoran Rekam Medis Menggunakan Metode Focus PDCA di RSUP Sanglah - Sedyo Pinerdi; Atma Deharja; Ervina Rachmawati (Politeknik Negeri Jember, 2020)
The duplication of medical record numbers during February 2020 at Sanglah Hospital reachs 7 cases, it iscaused by the mistake of the officer register patients at SIMARS and the handling of duplicate cases that doesnot optimal. The purpose of this study was evaluated the patient's medical record numbering system used theFOCUS PDCA method at Sanglah Hospital. This type of the study is qualitative. The data collecting methodused in this study were observation and interviews. The data analysis stage in this research included aninvestigation stage to find, organized, clarify, understand, select, plan, do, check, dan action. The results ofthis study were duplicate cases that occur because patients were uncooperative when discussed with officers,patient did not register, officers were not thorough, authentication systems for patient search menu was notintegrated, the absence of regulations regarding the handling of cases of duplicate medical record numbers,and duplicate case reporting only limited to merge medical record files. The solutions chosen to solve theproblem were developing SIMARS registration menu, making SOP for handling duplicate cases of SanglahHospital medical records, and making menu recording and reporting of duplicate medical record numbercases in E-PASTI.The planning done is an analys of the needs of emergency room registration officers,discussion of SOP design for handling duplicate medical record number cases, and analys the staff's needsfor the development of E-PASTI that results. The next stage is to give an advice in the IT field to developSIMARS in the patient registration search menu, request SOP authorization for the handling of duplicatemedical record number cases for the head of the medical record, and implement the menu recording andreporting of duplicate medical record number case cases.